Religious Parties and the Construction of Political Identity: A Comparative Study of Indonesia and Türkiye - Tabina, Athifa Sharanda Putri; Fahadayna, Adhi C.; Aminuddin, M. Faishal (Jurnal Politik, 2025)
This study examines the influence of religious-based political parties on political identity by comparing Indonesia and Türkiye. The background of this research lies in the role of religious parties in shaping political identity in Muslim-majority countries, where these parties must balance their adherence to religious doctrine with democratic values. The research problem examines how religious-based parties, such as PKS in Indonesia and AKP in Türkiye, construct their political identities within differing political systems. Using a quantitative approach with a comparative design and linear regression analysis, the study tests the impact of variables such as religious representation, associational networks, political education, and religious political identity. The results reveal that in Indonesia, these variables significantly shape political identity, whereas in Türkiye, no significant influence is observed due to AKP’s reliance on populist-nationalist narratives. The conclusion highlights that institutional and historical contexts heavily mediate the impact of religious parties on political identity.